RANCANG BANGUN APLIKASI PENGENALAN WAJAH UNTUK SISTEM PRESENSI DI PRODI TEKNIK INFORMATIKA UNIVERSITAS ISLAM RADEN RAHMAT MALANG MENGGUNAKAN METODE LBPH DAN LIBRARY OPENCV BERBASIS ANDROID - Wulandari, Gresy Ayu; Akbar, Muhammad Sonhaji; Tasaufi, Bila Nastiti (Universitas Methodist Indonesia, 2023)
The attendance system is a mechanism to record the attendance of students in each class they take. The attendance system serves as evidence of students' presence in the learning process. In its journey, Universitas Islam Raden Rahmat has been using manual attendance through attendance journals in the learning process. However, with technological advancements, the attendance process has followed this trend, one of which is face recognition. In this research, the researcher designed a face recognition application for the attendance system that can be implemented on mobile platforms, especially Android. This application using the Local Binary Pattern Histogram (LBPH) method and the OpenCV library. The objective of this application is to enhance the flexibility and efficiency of the current attendance system by eliminating the need to repeatedly retrieve attendance forms, preventing fraud, and reducing paper usage. By using the waterfall system development method, testing showed a face recognition accuracy of 70%